Prenatal sonography of multicentric infantile myofibromatosis: Case report and review of the literature. Issue 8 (9th May 2019) - Rekawek, Patricia; Coleman, Beverly G.; Kamath, Amita; Stone, Joanne L.
Abstract: Scant literature exists on prenatally diagnosed infantile myofibromatosis (IM). We report a case of multicentric IM, which was first recognized as a soft‐tissue paraspinal mass on prenatal sonography and subsequently characterized by MRI with pathological confirmation.